A Review of the Hybrid Darrieus-Savonius Turbine for Hydrokinetic Applications - Maldar, N.R. (Institute of Electrical and Electronics Engineers Inc., 2021)
In recent years, the cross-flow hydrokinetic turbines (HKTs) have been researched intensively owing to their key characteristics such as independency of flow direction and simple design. The Savonius turbine, being a drag-based device is known to have good starting performance. On the other hand, the lift-based Darrieus turbine, in several studies, has demonstrated reasonable efficiency over a wide range of flow velocities. To capitalize on the respective advantages, both the devices can be integrated together on the same axis thus forming a combined/hybrid turbine. In this paper, the authors have collected and analyzed published studies that investigate the performance of such hybrid Savonius-Darrieus designs with respect to hydrokinetic applications. Hardly a review study exists hitherto which solely discusses the studies for hybrid turbine that have been conducted using water as the operating fluid. Therefore, the primary aim of this paper is to establish a distinct research background for the hybrid turbine exclusively in terms of hydrokinetic applications. In addition to summarizing the existing literature, the present study also highlights the key gaps that will further enable the concerned researchers to explore the uninvestigated aspects within the domain of hybrid HKTs. Â© 2021 IEEE.